Can someone break down the steps in this please i understand it but i want to be prepare fully for further questions like this...... 2x - y=9, 3y + x =1 ....i got through bit of it...but i dont understand how when you take 1-3y and subsititue for x ....2(1-3y)-y =9...when you expand the brackets you get 2- 6y-y=9..... that last part i typed out i dont understand..please help

Guest Mar 25, 2019

#2**+2 **

So we have 2x - y = 9 and 3y + x = 1. Take the first one, and solving for y gets us y = 2x - 9. Substitute this into the second equation, and you have 3(2x - 9) + x = 1. Simplifying the left hand side gets us 6x - 27 + x = 1. 7x = 28. x = 4. Put this into either one, (I'm going to use the first) and you get 2(4) - y = 9,

8 - y = 9, -y = 1, so y = -1 and you can check this by putting both values of x and y into either equation.

x = 4

y = -1

Hope this helps!

LagTho Mar 25, 2019